Development of Teaching Materials Based on Social Values of Banjar Community to Improve Students' Financial Literacy - Herry Porda Nugroho Putro; Raihanah Sari; Muhammad Rezky Noor Handy; Sumiati Sumiati; Hijjatul Alawiah; Ananda Firda Afifah; Rezky Anisa (Universitas Lambung Mangkurat, 2024)
Financial literacy is an essential skill to equip students with the knowledge and skills needed to manage finances. The gap in understanding financial literacy among junior secondary level students reflects the urgent need to introduce innovative and effective learning teaching materials. This research was conducted with the aim of increasing students' financial literacy through the application of the Project Based Learning model. This research method is Research and Development (R&D) which adopted the 4D model of Thiagarajan, Semmel & Semmel in 1974. Validation of the teaching module was carried out by two expert lecturers and teacher response data was validated by two class IX junior high school teachers. Data analysis involves qualitative descriptive analysis techniques and descriptive statistics, including evaluation of validation results by experts and analysis of teacher responses. The results of the research show that teaching materials from the material aspect have an average Aiken's V value of 0.90 (Very Valid). In the language aspect of teaching materials, the average Aiken's V value is 0.89 (Very Valid). Teacher responses to teaching materials reached an average percentage of 85.25% (Very Good). Based on the results of this research, it can be concluded that this research has succeeded in developing teaching materials based on the social values ofthe Banjar community to increase students' financial literacy.